A rare case of newly diagnosed multiple myeloma presenting to the emergency department with acute paraplegias - Yıldırım, Sunay; Yeniocak, Selman; Ayer, Mesut; Az, Adem; Özden, Muhammed; Demirel, Ahmet (Journal of Surgery and Medicine, 2019)
Multiple myeloma (MM), neoplastic proliferation of monoclonal plasma cells in bone marrow, constitutes 1% of cancers. We discuss a rare case of newly diagnosed MM presenting to the emergency department with sudden strength loss in both legs and inability to walk, together with the current literature. Impaired balance and 2/5 strength loss in the bilateral lower extremities was determined in a 42-year-old man presenting due to weakness in both legs and inability to walk, noticed on waking in the morning. At blood tests, uric acid was 8.4 mg/dl, total protein 98.8 g/L, globulin 60.8 g/L. Magnetic resonance imaging revealed a mass between T2 and T4 vertebrae. At mass biopsy immunohistochemical investigation, lesion cluster of differentiation (CD)38, CD138, endomysial antibody, kappa and lambda cells exhibited immune reactions. Serum IgA was 0.27 g/L, IgM 0.28 g/L, IgG 44.36 g/L, beta-2 microglobulin 4.78 mg/L, lambda light chain 0.230 g/L, and kappa light chain 5.25 g/L. Mass biopsy revealed plasma cell tumor, with atypical plasma cells at 52%, which was compatible with MM at bone marrow aspiration biopsy. Neoplastic plasma cell proliferation should be considered for differential diagnosis in sudden strength loss in the lower extremities.